2016
DOI: 10.1007/s12119-016-9360-3
|View full text |Cite
|
Sign up to set email alerts
|

Risky Sexual Behaviour Among Married and Cohabiting Women and its Implication for Sexually Transmitted Infections in Mahikeng, South Africa

Abstract: Risky sexual behaviour continues to be the main means through which sexually transmitted infections (STIs) and HIV are spread in South Africa. However few studies have assessed risky sexual behaviour among married and cohabiting women in this high HIV prevalence country. The aim of this study was therefore to assess the prevalence and identify the predictors of risky sexual behaviour among married and cohabiting women in Mahikeng Local Municipality where HIV is generalized. The study used cross-sectional mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The results of this study suggest that female students who were single or not married were most likely staying with sexual partners in their residences around while at college. The results of this study concur with the results of various studies [6,15,16]. Furthermore, in their studies [6,15,16] it is stipulated that women who stay with their partners or who were married were engaging in risky sexual behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study suggest that female students who were single or not married were most likely staying with sexual partners in their residences around while at college. The results of this study concur with the results of various studies [6,15,16]. Furthermore, in their studies [6,15,16] it is stipulated that women who stay with their partners or who were married were engaging in risky sexual behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…The detailed sampling of the methodology has been published in an article called ‘Risky sexual behaviours among married and cohabiting women and its implication for sexually transmitted infections in Mahikeng’. 27 …”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the study also found that those who are ever married or cohabiting are less at risk of engaging in risky sexual behaviour. The finding of the less-prevalence of risky sexual behaviour among married people is in converse with Osuafor & Ayiga's (2016) study of married and cohabiting women in Mahikeng, South Africa. This suggests that marriage prevent people from engaging in unsafe sex.…”
Section: Discussionmentioning
confidence: 50%